EVIDENCE BASED LEARNING: AN ANALYSIS OF IMPACT ON RETENTION OF KNOWLEDGE - Thote, Prashant; S, Gowri (International Journal of Research -GRANTHAALAYAH, 2020)
Chemistry is a fundamental discipline of Science that accounts for day to day life at molecular level. The major challenge in the classroom instructions is to bridge the gap between high demand of learning and low efforts of learners due to lack of motivation. In this paper attempt is made to correlate the subject with day to day life. The objectives of the classroom instructions are to make effective and efficient delivery of instruction, knowledge, skill, attitude and competence. The aim of the present study is to make Chemistry subject vivid, joyful understanding of concept to stimulate learners intellectual curiosity to enhance the learning. In this study total 50 students participate. The students are categorized into two groups (study group and the control group). Each group consists of 25 students. Quasi experiment research design is applied. Data is collected by using question paper based on Revised Bloom’s Taxonomy (RBT) before and after the experiment. Result of the study reveals that the evidence-based learning approach is used for the classroom instructions and has positive impact on motivation, satisfaction and academic achievement. The present classroom instruction is beneficial because it correlates the subject with day today life and arouses the interest among the learners. Based on the findings of the study some suggestions are made.